TINJAUAN LOKASI PARKIR PADA RUAS JALAN HOS COKROAMINOTO KISARAN KABUPATEN ASAHAN - Satriawan Lubis, Kenny; Sihombing, Alexander Tuahta; Hamzah, Amir (Jurnal Bidang Aplikasi Teknik Sipil dan Sains (BATAS), 2025)
This study aims to analyze parking characteristics and their impact on traffic performance on street HOS Cokroaminoto, Kisaran, Asahan Regency. This location is an area with quite high trade and culinary activities, so that the roadway is often used as a parking area. The problem that arises is the reduction in the effective width of the road which impacts the smooth flow of traffic. The research method used is a field survey approach by conducting direct observation of parking activities at three research locations. Data collected include the volume of vehicles entering and exiting, parking duration, parking accumulation, and parking turnover rate. The analysis was conducted using the guidelines of the Directorate General of Land Transportation (1996) and the Regulation of the Minister of Transportation Number 34 of 2014 concerning parking management. The results of the study indicate that parking activities on Jalan HOS Cokroaminoto have not been optimally organized. The parking patterns used are mostly perpendicular (90°) for motorcycles and parallel for cars. The parking turnover rate is relatively low, indicating inefficient vehicle turnover and causing limited parking space. Based on the analysis, it can be concluded that parking activity on street HOS Cokroaminoto has reduced road capacity and reduced traffic flow